The role of peer observation and peer feedback in the promotion of self-regulated learning: An integrative review - Santos, A. C.; Torres, A. C.; Nobre, A.; Mouraz, A. (International Journal of School and Educational Psychology, 2025)
Self-regulated learning (SRL) involves the cognitive, metacognitive, emotional, and behavioral dimensions of knowledge acquisition and predicts academic achievement. This process can be enhanced through collaboration, particularly peer observation and feedback. Despite extensive research on SRL, the impact of peer observation and feedback in secondary education has been underexplored. This review aims to map the existing literature and analyze factors affecting SRL development through peer observation and feedback in secondary education, employing a systematic search adhering to PRISMA guidelines. Eighteen studies from seven databases, published between 2012 and 2023, were selected, involving 1,132 students aged 13 to 18 across various fields (e.g. mathematics, sciences, languages, arts). Most studies focused on upper secondary school (66.7%). Results indicate that peer observation and feedback have a positive impact on SRL. Collaborative activities were common, with some using inquiry-based, constructivist, or reflective learning strategies. Most studies explicitly described peer feedback, while peer observation was often implicit. Effective SRL promotion requires systematic, intentional collaboration led by motivated teachers. High subject-related confidence, academic engagement, and strong social and emotional skills, such as self-awareness and communication, further support SRL. This review highlights the importance of integrating structured peer observation and feedback into educational policies to optimize lifelong learning.